DNA Methylation Changes Are Associated With an Incremental Ascent to High Altitude - Childebayeva, Ainash; Harman, Taylor; Weinstein, Julien; Goodrich, Jaclyn M.; Dolinoy, Dana C.; Day, Trevor A.; Bigham, Abigail W.; Brutsaert, Tom D. (Frontiers in Genetics, 2019)
Genetic and nongenetic factors are involved in the individual ability to physiologically acclimatize to high-altitude hypoxia through processes that include increased heart rate and ventilation. High-altitude acclimatization is thought to have a genetic component, yet it is unclear if other factors, such as epigenetic gene regulation, are involved in acclimatization to high-altitude hypoxia in nonacclimatized individuals. We collected saliva samples from a group of healthy adults of European ancestry (n = 21) in Kathmandu (1,400 m; baseline) and three altitudes during a trek to the Everest Base Camp: Namche (3,440 m; day 3), Pheriche (4,240 m; day 7), and Gorak Shep (5,160 m; day 10). We used quantitative bisulfite pyrosequencing to determine changes in DNA methylation, a well-studied epigenetic marker, in LINE-1, EPAS1, EPO, PPARa, and RXRa. We found significantly lower DNA methylation between baseline (1,400 m) and high altitudes in LINE-1, EPO (at 4,240 m only), and RXRa. We found increased methylation in EPAS1 (at 4,240 m only) and PPARa. We also found positive associations between EPO methylation and systolic blood pressure and RXRa methylation and hemoglobin. Our results show that incremental exposure to hypoxia can affect the epigenome. Changes to the epigenome, in turn, could underlie the process of altitude acclimatization.